Dermatoglyphic Appraisal of Multiple Births Women in Igbo-Ora & Ogbomosho, Nigeria - Kehinde T. Adenowo; Olugbenga O. Eweoya; Olugbemi T. Olaniyan; Abayomi Ajayi (Advancement and New Understanding in Medical Science Vol. 9, 2024)
The scientific study of epidermal ridges on the palms and toes is termed dermatoglyphics. Multiple births occur when more than one fetus results from a single pregnancy. This chapter highlights the relationship between multiple births and palmar flexion creases. The study used a cross sectional case control conducted on volunteers from Igbo-Ora and Ogbomosho in Oyo State, Nigeria. Two hundred (200) Igbo-Ora and one hundred (100) Ogbomosho healthy and consenting adult female indigenes aged between 25-50 years who have completed their families were recruited for the study. The subjects were grouped into four; group I consisted of women who had given birth to twins in Igbo-Ora; group II consisted of women who had never given birth to twins in Igbo-Ora; group III consisted of women who had given birth to twins in Ogbomosho; group IV consisted of women who had never given birth to twins in Ogbomosho. The sample size of the participants was calculated by Yamane equation at 95% confidence level, and 399 subjects were needed, their bio-data were obtained using a structured questionnaire to which they supplied answers. Dermatoglyphics prints were taken by the ‘Ink. A total of 400 and 200 respective palms of Igbo-Ora and Ogbomosho subjects comprising both hands were subjected to dermatoglyphic analysis using magnifying hand lens. The samples were analysed grossly for the number of primary palmar flexion creases P, intersection, I, of primary palmar flexion creases and complete transverse flexion creases, C. Dermatoglyphic patterns of 105 (Igbo-Ora) and 50 (Ogbomosho) women with multiple births were compared with 95 (Igbo-Ora) and 50 (Ogbomosho) women with single births. Palm print patterns of 105 (Igbo-Ora) and 50 (Ogbomosho) women with multiple births were compared with 95 (Igbo-Ora) and 50 (Ogbomosho) women with single births. The percentage (number) of primary, P and intersection, I of palmar creases with complete transverse creases, C (PIC) 300 bilaterally was significantly greater (p < 0.005) in the hands of Igbo-Ora multiple births women (52.4 %) than their single births women (37.4%) while same trend was observed for Ogbomosho women although difference was statistically insignificant, (p > 0.005). In both Igbo-Ora and Ogbomosho women, PIC 310 bilaterally was found to be significantly higher (p < 0.05) in both hands of single births women than the multiple (births)birth women. This chapter finally concluded by showing the relationship between a woman’s tendency to give birth to multiples and dermatoglyphics (which is a simple non-invasive, inexpensive anatomical marker).